Middle class China : identity and behaviour - Chen, Minglu; Goodman, David S. G. (Cheltenham : Edward Elgar, 2013)
A general expectation has developed that China's middle class will generate not only social but also political change. This expectation often overlooks the reality that there is no single Chinese middle class with a common identity or will to action. This timely volume examines the behaviour and identity of the different elements of China's middle class entrepreneurs, managers, and professionals in order to understand their centrality to the wider processes of social and political change in China. The expert contributors seek to identify the social space occupied by the Chinese middle class rather than identifying social backgrounds and attitudes. In so doing they explore socio-political issues, the development of a consumer society, relationships between gender and class in the workplace, home-ownership and the appearance of gated communities, and the political interaction between the Party-state and the entrepreneurial middle classes and their impact on the new institutional economics. Providing a more nuanced understanding of the structure of the middle class in China and identifying dynamic elements in their behaviour, this unique book will prove a fascinating and thought provoking read for academics, students and researchers with an interest in Asian studies and public policy.
Machine generated contents note: 1.Sociopolitical attitudes of the middle class and the implications for political transition / Li Chunling -- 2.Class, consumption and the economic restructuring of consumer space / Carolyn Cartier -- 3.Urban housing-status-groups: consumption, lifestyles and identity / Beibei Tang -- 4.White-collar workers: gender and class politics in an urban organization / Jieyu Liu -- 5.The socioeconomic status, co-optation and political conservatism of the educated middle class: a case study of university teachers / Jonathan Unger -- 6.Homeowners' movements: narratives on the political behaviours of the midd le class / Jean-Louis Rocca -- 7.Institutional determinants of the political consciousness of private entrepreneurs / Hans Hendrischke -- 8.Understanding entrepreneurs / Dai Jianzhong.
Includes bibliographical references (p. 169-193) and index.
Keywords: Middle class -- China